Policy for sustainable consumption – an assessment of Swedish municipalities - Dawkins, Elena; André, Karin; Leander, Elin; Axelsson, Katarina; Gerger Swartling, Åsa (Frontiers in Sustainability, 2023)
Municipalities have a key role to play in developing and implementing policy for sustainable consumption, yet the evidence on the extent of municipalities’ work in this area and the constraining and enabling factors they face in this endeavour is sparse. This study examines municipal policies for sustainable consumption and their implementation, using food consumption in Sweden as an example. It combines data from a nationwide survey, policy document analysis, and a two-year in-depth investigation into two municipalities that serve as case studies. Findings show that Swedish municipalities have several policies in place related to sustainable food consumption. They use multiple policy instruments to target specific areas of food consumption, and are positive about their current and potential impact in specific areas such as sustainable school meals and tackling food waste. However, municipalities face multiple challenges in delivering sustainable food consumption, including lack of resources and knowledge in some areas. If there is a lack of political support it can also be an major inhibiting factor. . The municipalities welcome national-level strategy, rules and regulations that are supportive of their goals.. They rely on good data collection and strong networks and stakeholder relationships to enable their work. Many of the latest recommendations for a comprehensive policy approach to sustainable food consumption are yet to be applied at the municipal level in Sweden. These include having a strong vision and strategic approach; expanded policy mix; the use of systems thinking and practices-based approaches for policy design; the adoption of more coercive policy instruments; and innovative methods to engage target groups beyond municipal operations. However, this study did reveal several existing areas where there are strong policy foundations from which these approaches might be developed. Tackling the identified constraints and expanding the enabling factors could further the work on sustainable food consumption at the municipal level in Sweden and provide insights for other countries and studies at the local level.